2010
DOI: 10.1002/hep.23327
|View full text |Cite
|
Sign up to set email alerts
|

Entecavir treatment for up to 5 years in patients with hepatitis B e antigen-positive chronic hepatitis B

Abstract: Sustained virologic suppression is a primary goal of therapy for chronic hepatitis B (CHB). In study entecavir (ETV)-C hronic hepatitis B (CHB) affects over 350 million people worldwide. Long-term complications of infection include cirrhosis and hepatocellular carcinoma (HCC), which together cause over 500,000 deaths annually. 1,2 CHB patients with an elevated viral load (ongoing viral replication) have the highest risk of progressing to these life-threatening complications. 3,4 To avoid or minimize liver dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
443
3
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 539 publications
(480 citation statements)
references
References 21 publications
23
443
3
11
Order By: Relevance
“…Recent liver society guidelines recommended the use of entecavir or tenofovir as first-line therapy in patients with chronic hepatitis B and an indication for nucleoside/nucleotide analogues, because both drugs potently inhibit the HBV reverse transcriptase and have a high barrier to resistance. Entecavir and tenofovir have been shown to efficiently maintain suppression of HBV DNA levels for prolonged periods of time in the vast majority of treated patients [17][18][19]. As a result, most patients who started therapy with other drugs currently receive entecavir and/or tenofovir as part of their treatment regimen in areas where these drugs are available and reimbursed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent liver society guidelines recommended the use of entecavir or tenofovir as first-line therapy in patients with chronic hepatitis B and an indication for nucleoside/nucleotide analogues, because both drugs potently inhibit the HBV reverse transcriptase and have a high barrier to resistance. Entecavir and tenofovir have been shown to efficiently maintain suppression of HBV DNA levels for prolonged periods of time in the vast majority of treated patients [17][18][19]. As a result, most patients who started therapy with other drugs currently receive entecavir and/or tenofovir as part of their treatment regimen in areas where these drugs are available and reimbursed.…”
Section: Discussionmentioning
confidence: 99%
“…Received August 10, 2012; accepted January 15, 2013. risk of drug resistance in long-term studies. 14,15 Histological improvement was observed in 66 of the 69 patients (96%) who had received entecavir for 3 to 7 years. 16 In a randomized trial of 191 patients with decompensated cirrhosis, entecavir-treated patients tended to have lower incidence of HCC than those treated with adefovir at 48 weeks.…”
mentioning
confidence: 97%
“…By sustained suppression of HBV DNA, achieving HBeAg and/or HBsAg SC, other studies have shown a reduction in fibrosis, as well as regression in cirrhosis (10,13,14). Along with this improved liver histology, it is logical to explain the improved liver function described above.…”
Section: Discussionmentioning
confidence: 95%